SOSIALISASI PENGGUNAAN KEYBOARD AKSARA BALI PADA TINGKAT SEKOLAH MENENGAH ATAS (SMA) - Pramartha, C.; Putra, I. G. N. A. C.; Suputra, I. P. G. H.; Supriana, I. W.; Arka, I. W. (Buletin Udayana Mengabdi; Vol 24 No 1 (2025): Buletin Udayana Mengabdi, 2024)
The socialisation and training activities focusing on the utilization of Balinese script keyboards in high schools within Badung Regency represent tangible steps towards implementing the outcomes of innovative research conducted at Udayana University in 2020 and 2021. Moreover, these initiatives aim to actualize the provisions stipulated in Regional Regulation Bali Province number 4 of 2020, which addresses the Strengthening and Advancement of Balinese Culture. Consequently, this undertaking not only reinforces the practical aspects of employing the Balinese script but also contributes to supporting regional policies dedicated to preserving and fostering Balinese culture.  The execution of this initiative spanned four months, adhering to meticulously prepared plans and guidelines established by the authors. The primary aspiration for this effort is its sustainability, prompting an evaluation at the conclusion of the activity. This evaluation is undertaken to refine training materials and methods that may require enhancement. The involvement of lecturers and students from two disciplines, namely FMIPA and FIB, is integral to this activity. Additionally, the engagement of decision- makers such as BRIDA and DISDIKPORA plays a pivotal role in the effective organization of this activity. Student participation has proven to positively impact the enhancement of their soft skills in practical settings. The enthusiasm and positive feedback received serve as clear indicators that this service activity is proceeding seamlessly and achieving notable success. Keywords: innovation research, keyboard, tamiang,  Balinese script, downstream